Pengaruh Net Ekspor dan Penanaman Modal Asing terhadap Cadangan Devisa Indonesia - Ratnasari, Erli Diah Ayu; aji, tony seno (Independent: Journal of Economics, 2023)
This study aims to determine the effect of net exports and foreign investment on Indonesia's foreign exchange reserves. This study uses a quantitative approach with data in the form of semi-annual time series from 2005 to 2021 in the form of net export data (total exports - total imports), realization of foreign investment and Indonesia's foreign exchange reserves. The analysis technique uses multiple linear regression with the Ordinary Least Square model. The results of the study show that the variables of net exports and foreign investment partially have a positive and significant effect on Indonesia's foreign exchange reserves. Meanwhile, through simultaneous testing, it was found that the variable net exports and foreign investment together had an effect on Indonesia's foreign exchange reserves with an effect of 0.860246 or 86%. These results indicate that an increase in net exports and foreign investment will have a positive impact on increasing the position of Indonesia's foreign exchange reserves.